Analisis Prioritas Kebutuhan Petani Kopi Organik di Kecamatan Sukorambi Kabupaten Jember Melalui Rantai Nilai - Renaldi, Muhammad; Muksin; Krismiratsih, Fitri (Politeknik Negeri Jember, 2023)
This research was conducted in Klungkung village and Krangpring Lor village, Sukorambi sub-district, Jember district, the method used in this research was descriptive qualitative. The data used is primary data through field surveys, interviews and questionnaires. Sampling was carried out using the purposive sampling method and snowball sampling technique. The analysis in this research includes Value chain mapping analysis and Hanlon Model Analysis for farmers, communities, and value chain actors and traders. The aim of this research is to analyze the value chain in organic coffee business activities and also identify priority problems that must be immediately resolved through value chain analysis. It is hoped that the results of this research will have a positive impact on organic coffee farmers in improving the people's economy.